The role of physical culture and sports in the formation of a well-rounded personality and a healthy lifestyle - Kiryanova L.A.; Korobov I.A.; Ivanova A.A.; Savchenko Yu.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to evaluate the role of physical culture in the formation of personality and a healthy lifestyle. Methods and structure of the study. Thestudy,devoted to the study of the influence of physicalcultureonpersonalitydevelopment,involvedstudents of the 5thgrade of secondaryschoolNo.6,locatedinSt.Petersburg. The results of the conductedresearchconvincinglydemonstratethatsportandphysicalcultureplay an importantrolein the formation of a harmoniouslydevelopedpersonalityandleading a healthylifestyle. Results and conclusions. Regular sports and physical exercises contribute to the improvement of physical qualities such as strength, endurance, flexibility, and maintain the required level of physical activity. In addition, physical activity has a positive effect on the development of a number of psychological qualities, including self-awareness, discipline, self-confidence and the ability to control their emotions. Awareness of the principles of healthy eating helped students maintain optimal weight or reduce excess body weight, as well as form healthy eating habits.